2020
DOI: 10.3389/fcell.2020.00056
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 37 Suppresses M1 Macrophage Polarization Through Inhibition of the Notch1 and Nuclear Factor Kappa B Pathways

Abstract: Macrophage-orchestrated chronic inflammation plays an important role in cardiovascular disease, including accelerating the development of calcific aortic valve disease (CAVD). M1 and M2 macrophage polarization imbalances can alter intensity of inflammatory responses. Recombinant human interleukin 37 (IL-37) could be involved in regulating immune cell function to attenuate inflammation. This study aimed to identify IL-37 specifically modulates M1 polarization and investigate the underlying mechanism. Compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 44 publications
4
49
0
Order By: Relevance
“…The imbalance of M1 and M2 macrophage polarization can affect the intensity of the inflammatory responses. Calcific aortic valves present a higher amount of M1 macrophages and less IL-37 expression compared to normal valves (48). RhIL-37 downregulates the expression of inducible nitric oxide synthase, CD11c, IL-6, and monocyte chemoattractant protein 1 (MCP-1) in M1 macrophage in vitro, and inhibits their polarization through the suppression of the activation of the Notch1 and NF-kB pathways (48).…”
Section: Il-37-induced Effects On Macrophagesmentioning
confidence: 99%
“…The imbalance of M1 and M2 macrophage polarization can affect the intensity of the inflammatory responses. Calcific aortic valves present a higher amount of M1 macrophages and less IL-37 expression compared to normal valves (48). RhIL-37 downregulates the expression of inducible nitric oxide synthase, CD11c, IL-6, and monocyte chemoattractant protein 1 (MCP-1) in M1 macrophage in vitro, and inhibits their polarization through the suppression of the activation of the Notch1 and NF-kB pathways (48).…”
Section: Il-37-induced Effects On Macrophagesmentioning
confidence: 99%
“…In addition, IL-37 can also inhibit the Notch signaling pathway. In fact, IL-37 inhibits M1 macrophage polarization by suppressing the Notch1 and NK-kB pathways (74). However, it has been found that IL-37 is almost not expressed in non-small cell lung cancer tissues, but is highly expressed in adjacent normal tissues (75).…”
Section: Notch Signalingmentioning
confidence: 99%
“…In vivo and in vitro models have demonstrated that low LAM concentration can induce a negative regulation of the activation of the immune system (Driss et al, 2012;Chávez-Galán et al, 2015;Yuan et al, 2019). Perhaps this is because LAM possess multiple epitopes, and these interact with cell surface receptors in different grades of affinity (Choudhary et al, 2018;De et al, 2020;Zhou et al, 2020).…”
Section: Lam: Origin and Structurementioning
confidence: 99%
“…Recently, it has been described that IL-37 suppresses activation, proliferation, and cytokine production through down-regulation of nuclear factor-kappa B (NF-κB), and that it inhibits macrophage polarization into the M1 subtype (Zhou et al, 2020). However, this immunomodulatory effect is not observed in A TB patients, who have high circulating levels of IL-37 but not a high expression of its receptors IL-18R and IL-1Ra; this is probably a regulatory mechanism exclusive of the alveolar region (Wawrocki et al, 2019;Moideen et al, 2020;Zhang et al, 2020).…”
Section: Modulation Of the Innate Immunity By Lammentioning
confidence: 99%